Low adherence to a new guideline for managing febrile infants ≤59 days - Elliver, Matilda; Norrman, Josefin; Orfanos, Ioannis (Frontiers in Pediatrics, 2024)
Background: Management of young febrile infants is challenging. Therefore, several guidelines have been developed over the last decades. However, knowledge regarding the impact of introducing guidelines for febrile infants is limited. We assessed the impact of and adherence to a novel guideline for managing febrile infants aged ≤59 days.This retrospective cross-sectional study was conducted in 2 pediatric emergency departments in Sweden between 2014 and 2021. We compared the management of infants aged ≤59 days with fever without a source (FWS) and the diagnosis of serious bacterial infections (SBIs) before and after implementing the new guideline.We included 1326 infants aged ≤59 days with FWS. Among infants aged ≤21 days, urine cultures increased from 49% to 67% (p=0.001), blood cultures from 43% to 63% (p<0.001), lumbar punctures from 16% to 33% (p=0.003), and antibiotics from 38% to 57% (p=0.002). Only 39 of 142 (28%) infants aged ≤21 days received recommended management. The SBI prevalence was 16.7% (95% CI, 11.0-23.8) and 17.6% (95% CI, 11.7-24.9) before and after the implementation, respectively. Among infants aged ≤59 days, there were 3 infants (0.6%; 95% CI, 0.1-1.7) in the pre-implementation period and 3 infants (0.6%; 95% CI, 0.1-1.7) in the post-implementation period with delayed treated urinary tract infections.Investigations and antibiotics increased significantly after implementation of the new guideline. However, doing more did not improve the diagnosis of SBIs. Thus, the low adherence to the new guideline may be considered justified. Future research should consider strategies to safely minimize interventions when managing infants with FWS.